Age-Related Effects on Language Production During Selective and Divided Attention Conditions: Implications for Aphasia Assessment. - McDonald, Emily; Harmon, Tyson G.; Bailey, Dallin J. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study was divided into two parts. Study 1 aimed to investigate how dual-task and select background noise conditions impact language production of neurologically healthy adults (NHA). Study 2 aimed to use the sample from Study 1 to identify whether four people with mild aphasia perform at an expected level when compared with their NHA peer group. Method: Study 1 examined the spoken language production of NHA in sustained, selective, and divided attention conditions during a story retell task. NHA participant groups consisted of 21 young and midlife adults (26-54 years), 19 early older adults (55-69 years), and 20 late older adults (70-85 years). Study 2 used a case series approach to investigate how the language production of four people with aphasia (PWA) compared to their respective NHA group. All participants retold stories in a silent baseline condition, three background noise conditions (cocktail party, conversation, phone call), and one dual-task condition (tone discrimination). Language production measures (language informativeness, lexical diversity, lexical--phonological errors, speech rate, disfluent verbalizations), tone discrimination accuracy and response time, and perceived effort and stress were compared across groups and conditions. Results: Study 1 revealed that the language of late older adults was significantly less efficient than the other two groups, that both late and early older adults produced more disfluent verbalizations than young and midlife adults, and that late older adults demonstrated more lexical diversity than early older adults. The tone discrimination accuracy and response time of late older adults were also significantly lower than those of young and midlife adults. Across groups, language informativeness decreased and lexical--phonological errors increased during the dual-task condition, and lexical diversity decreased while lexical--phonological errors and disfluent verbalizations increased during the phone call condition. Costs to tone discrimination accuracy, tone discrimination response time, perceived effort, and perceived stress were found in the dualtask condition across groups. In Study 2, four PWA showed impaired language production when compared with their age-matched NHA group across multiple dependent variables with somewhat unique responses for each participant. Ultimately, three of the four showed some degree of interference in the attentionally demanding conditions, whereas one showed some degree of benefit. Conclusions: The findings of Study 1 suggest that some, but not all, measures of spoken language production are impacted by aging, and that selective and divided attention interfere with spoken language production for NHA. Study 2 suggests that although attentional demands may disproportionately affect error production for many PWA, some may also experience benefits to their spoken language during attentionally demanding conditions. These findings emphasize the importance of individualized evaluation of the impact of everyday communication environments for PWA. Supplemental Material: https://doi.org/10.23641/asha.31804207